2020
DOI: 10.1097/brs.0000000000003628
|View full text |Cite
|
Sign up to set email alerts
|

Frameless Patient Tracking With Adhesive Optical Skin Markers for Augmented Reality Surgical Navigation in Spine Surgery

Abstract: Study Design. Observational study. Objective. The aim of this study was to evaluate the accuracy of a new frameless reference marker system for patient tracking by analyzing the effect of vertebral position within the surgical field. Summary of Background Data. Most modern navigation systems for spine surgery rely on a dynamic reference frame attached to a vertebra for tracking the patient. This solution has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…When using manual registration and direct surface tracking, the AR image is manually adjusted to match the reality thereby inducing a potential registration error. Intraoperative imaging in combination with optical markers or a DRF, however, allows for an accurate automatic coregistration [7,10]. Nonetheless, an isolated comparison between Monitor-AR and HMD-AR on the one hand, and optical markers and surface tracking on the other hand, cannot be performed on the currently available data.…”
Section: Discussionmentioning
confidence: 99%
“…When using manual registration and direct surface tracking, the AR image is manually adjusted to match the reality thereby inducing a potential registration error. Intraoperative imaging in combination with optical markers or a DRF, however, allows for an accurate automatic coregistration [7,10]. Nonetheless, an isolated comparison between Monitor-AR and HMD-AR on the one hand, and optical markers and surface tracking on the other hand, cannot be performed on the currently available data.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy, of roughly 0.6 mm at skin level, achieved with the current framework should be seen in light of previous results obtained by the ARSN system relying on adhesive skin markers. In a recent study using ARSN, Burström et al [32] demonstrated a technical accuracy of 0.94 ± 0.59 mm and 1.97 ± 1.33 mm, respectively, for cadaveric and clinical cases of pedicle screw placement. The difference in accuracy, could be attributed to the actual placement of pedicle screws in a clinical situation.…”
Section: Discussionmentioning
confidence: 98%
“…16 Other groups have advocated the use of fiducial CT markers to improve spatial and temporal registration efficiency. 26,27 However, this approach poses its own set of challenges, including the need to obtain additional CT scans of the patient specifically dedicated to the registration effort. Placement of deep brain stimulation electrodes is one such example in which this technology has an advantage over current frame-based or frameless methods, which require additional CT scans and fiducial markers.…”
Section: Discussionmentioning
confidence: 99%